Analisis Perilaku Investor dalam Pasar Saham: Pendekatan Islam untuk Meningkatkan Stabilitas Keuangan - Suryani, Dewi; Umuri, Khairil; Sartiyah (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study explores the impact of investor behavior on stock market stability through the lens of Islamic principles, emphasizing justice and transparency. Employing a systematic literature review approach, the research analyzes 200 relevant articles from 2019–2023 to investigate the relationship between investor behaviors—such as speculation and gharar (uncertainty)—and market volatility. The data were derived from a comprehensive scholarly literature review, including academic journals, articles, books, and research reports. By synthesizing relevant sources, the study offers an in-depth understanding of investor behavior and the implications of Islamic perspectives on stock market stability. The findings reveal that behaviors aligned with Shariah principles, including avoiding speculation and reinforcing transparency, contribute significantly to enhancing stock market stability. Moreover, the study underscores the importance of implementing Shariah-based regulations and promoting Islamic financial literacy to support ethical investment practices. The practical implications of this research include recommendations for regulators to integrate Shariah ethical standards into market policies and encourage market participants to adopt fundamental analysis consistent with Shariah principles. Finally, the study opens avenues for future research to explore empirical applications in specific stock markets and their impact on sustainable economic policies.